2014
DOI: 10.1093/ije/dyu094
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic position, lifestyle factors and age at natural menopause: a systematic review and meta-analyses of studies across six continents

Abstract: Background: Age at natural menopause (ANM) is considered a marker of biological ageing and is increasingly recognized as a sentinel for chronic disease risk in later life. Socioeconomic position (SEP) and lifestyle factors are thought to be associated with ANM.Methods: We performed a systematic review and meta-analyses to determine the overall mean ANM, and the effect of SEP and lifestyle factors on ANM by calculating the weighted mean difference (WMD) and pooling adjusted hazard ratios. We explored heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
291
7
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(336 citation statements)
references
References 79 publications
23
291
7
15
Order By: Relevance
“…Consequences of malnutrition such as frailty, sarcopenia, osteoporosis and chronic morbidity will be experienced by the older adult at an earlier age, only because of his/her socioeconomic condition. 39 It has been reported that the SFFQ instrument underestimates energy intake. OA are more vulnerable to memory bias and underreport energy.…”
Section: Discussionmentioning
confidence: 99%
“…Consequences of malnutrition such as frailty, sarcopenia, osteoporosis and chronic morbidity will be experienced by the older adult at an earlier age, only because of his/her socioeconomic condition. 39 It has been reported that the SFFQ instrument underestimates energy intake. OA are more vulnerable to memory bias and underreport energy.…”
Section: Discussionmentioning
confidence: 99%
“…For age at natural menopause, several recent large prospective studies and meta-analyses reiterate the effects of active smoking on the timing of menopause 31 33–36. Biologically, tobacco toxins negatively affect the hormonal milieu through differing mechanisms, and various studies have investigated levels of oestrone, oestradiol, oestriol, progesterone, follicle-stimulating hormone, luteinising hormone, and anti-Müllerian hormone (a direct measure of ovarian reserve); the results predict an early end to the reproductive life of the ovaries and uterus in women exposed to active smoke and SHS 7–10 37–39.…”
Section: Discussionmentioning
confidence: 99%
“…Age at menarche was included in models examining age at natural menopause. Potential confounders were primarily chosen based on a review of the literature discussed above, and we included potential confounders commonly used in analyses related to these outcomes 31. Potential confounders considered but not in the final adjustment models were age at first and last term birth, any induced abortions, parity, number of term births, income at baseline, BMI at 35 years and very hard exercise 3 or more times per week at 35 years.…”
Section: Methodsmentioning
confidence: 99%
“…It is unclear how these translate for the woman that smokes cigarettes while attempting to conceive; however, it is known that smoking leads to a reduction in ovarian reserve and an advancement of the age of menopause for the woman (167,301), potentially due to the influence of polycyclic hydrocarbons which are activated into more toxic metabolites by the liver (49,271). Further human studies have demonstrated that oocytes derived from cigarette smoking women undergoing IVF treatment have a greater number of immature oocytes (385), an increased thickness of the zona pellucida (310), with follicles containing higher level of markers of oxidative stress within the follicular fluid (252), and within the cumulus (316).…”
Section: Ovarian Functionmentioning
confidence: 99%